MRI denoising: a sparse ICA-based dictionary learning approach. (2nd June 2022) - Arathi, T.; Rahul, C.
Image denoising is the process of removing noise from an image and is basically a trade-off between noise removal and preservation of significant image details. This paper presents a new sparse processing-based denoising algorithm, the multi-median variance-independent component analysis (MMV-ICA) denoising algorithm. Various noises which affect medical images are also considered. The proposed denoising algorithm is based on sparse and redundant representations over learned dictionaries. MMV-ICA algorithm presented in this paper makes use of a patch-based dictionary creation method. The paper presents the results of MMV-ICA denoising technique, which are found to be in par with the existing sparse-based denoising methods.